Bio-Efficacy of Hexadecanoic Acid on Larvicidal, Pupicidal and Repellent Activities against Malarial Vector, Anopheles Stephensi (Liston). (Diptera: Culicidae) - Junaid Hassan; Arulsamy Jebanesan (International Journal of Pharma and Bio Sciences, 2022)
Mosquitoes have an important role in spreading the deadly diseases such as malaria, Japanese encephalitis, dengue and filariasis etc. Malaria is the most vulnerable public health problem of present time. Malaria is caused by malarial parasite plasmodium falciparum and is one of the leading causes of human morbidity and mortality from infectious disease, predominantly in tropical and sub-tropical countries. Chemicals involved in insect communication are called Semiochemicals. Semiochemicals are organic compounds used by insects to convey specific chemical messages that modify behaviour or physiology. Semiochemicals are used as fastest growing materials due to their unique physical, chemical and biological properties. Hexadecanoic acid is a novel semiochemical which was not fully evaluated against the malarial vector Anopheles stephensi. The aim and objective of the present study was to evaluate the bio-efficacy of Hexadecanoic acid against the malarial vector Anopheles stephensi. Hexadecanoic acid was screened to assess Larvicidal, efficacy against the 3rd instar larvae and pupicidal activity at different concentrations ranging from 5-45 ppm against malarial vector Anopheles stephensi after 24h .The repellent activity was also assessed against An. stephensi at three different concentrations viz., 1.0, 2.0 and 4.0 mg/cm2 of treatment after 24h under the laboratory conditions. The compound was found to be effective against the mosquito. The LC50 and LC90 values for larvicidal bio-assay were 16.309, 28.624 ppm and for pupicidal bio-assay 30.311, 42.776 ppm respectively. Hexadecanoic acid also showed higher repellency with the increase in concentration. The highest repellency was observed at a concentration of 4.0mg/cm2 provided 100 percent protection up to 120 min against An. stephensi. Hence the results revealed that the Hexadecanoic acid is potential compound for controlling the vector mosquito.